Cost effectiveness of telehealth for patients with long term conditions (Whole Systems Demonstrator telehealth questionnaire study): nested economic evaluation in a pragmatic, cluster randomised controlled trial. - Henderson, C; Knapp, M; Fernández, J; Beecham, J; Hirani, S; Cartwright, M; Rixon, L; Beynon, M; Rogers, A; Bower, P; Doll, H; Fitzpatrick, R; et al. (2013)
OBJECTIVE: To examine the costs and cost effectiveness of telehealth in addition to standard support and treatment, compared with standard support and treatment. DESIGN: Economic evaluation nested in a pragmatic, cluster randomised controlled trial. SETTING: Community based telehealth intervention in three local authority areas in England. PARTICIPANTS: 3230 people with a long term condition (heart failure, chronic obstructive pulmonary disease, or diabetes) were recruited into the Whole Systems Demonstrator telehealth trial between May 2008 and December 2009. Of participants taking part in the Whole Systems Demonstrator telehealth questionnaire study examining acceptability, effectiveness, and cost effectiveness, 845 were randomised to telehealth and 728 to usual care. INTERVENTIONS: Intervention participants received a package of telehealth equipment and monitoring services for 12 months, in addition to the standard health and social care services available in their area. Controls received usual health and social care. MAIN OUTCOME MEASURE: Primary outcome for the cost effectiveness analysis was incremental cost per quality adjusted life year (QALY) gained. RESULTS: We undertook net benefit analyses of costs and outcomes for 965 patients (534 receiving telehealth; 431 usual care). The adjusted mean difference in QALY gain between groups at 12 months was 0.012. Total health and social care costs (including direct costs of the intervention) for the three months before 12 month interview were £1390 (€1610; $2150) and £1596 for the usual care and telehealth groups, respectively. Cost effectiveness acceptability curves were generated to examine decision uncertainty in the analysis surrounding the value of the cost effectiveness threshold. The incremental cost per QALY of telehealth when added to usual care was £92 000. With this amount, the probability of cost effectiveness was low (11% at willingness to pay threshold of £30 000; >50% only if the threshold exceeded about £90 000). In sensitivity analyses, telehealth costs remained slightly (non-significantly) higher than usual care costs, even after assuming that equipment prices fell by 80% or telehealth services operated at maximum capacity. However, the most optimistic scenario (combining reduced equipment prices with maximum operating capacity) eliminated this group difference (cost effectiveness ratio £12 000 per QALY). CONCLUSIONS: The QALY gain by patients using telehealth in addition to usual care was similar to that by patients receiving usual care only, and total costs associated with the telehealth intervention were higher. Telehealth does not seem to be a cost effective addition to standard support and treatment. TRIAL REGISTRATION: ISRCTN43002091.